The Wooden Skull: An Innovation through the Use of Local Materials and Technology to Promote the Teaching and Learning of Human Anatomy - Mugagga, Kintu; Mwarisi, Masilili G.; Dare, Samuel S. (BioMed Research International, 2020)
Skeleton models are important in facilitating a student’s easy retention and recollection of information in the future. These may assist students carry out hands-on practice in order to acquire and practice new skills that are relevant to first aid. The increasing number of medical institutions and medical students attracts the challenge of inadequate facilitation of the teaching and learning processes. This warrants a study and/or an exploration of an alternative solution such as wooden models in order to solve the problem of scarce and ethically restricted human teaching aids. Wooden pieces (50 cm length × 20 cm diameter) from a Jacaranda mimosifolia tree were prepared for the carving process, and wooden replicas of human skulls were made. Two experimental groups of randomly selected medical students (60: active and 60: control) were separately taught using wooden and natural skull models, respectively. The two groups were assessed and evaluated using the natural skull models to compare their understanding of the anatomy of the skull. Additionally, opinion statements were collected from participants in the active group during the oral examination. Six (6) wooden skull models were produced and used for experimental study. Comparisons of academic scores (mean and median) between active (students using the wooden skull) and control (students using natural skull) groups showed no statistically significant difference (P ≥ 0:05). Concerning the enhancement of learning skills, the wooden model was constructed in a way that would be able to enhance learning as it would be the natural skull. The wooden skull model, with more improvement in structural formation, can adequately facilitate the teaching and learning of anatomy of the human skull. This project and the experimental study about utilization of the wooden skull model provide a good potential of using the wooden models to supplement the use of the natural human skull.
Keywords: Wooden Skull; Local Materials; Teaching and Learning; Human Anatomy